O ensino de filosofia como prática de letramento e suas implicações educacionais para o pensar: o ensino de Filosofia na Unidade Integrada Doutor Almada Lima Filho - SILVA, Jônatas Viégas da (2019)
The present research aims at the study of literacy practices, which are characterized by emphasizing the social practice of reading and writing and for conceiving knowledge as something dialectically (re) constructed and (re) contextualized and above all its implications in the process of teaching-learning of the discipline philosophy in elementary school final grades. Driven by the students 'real needs (6th year), it was possible to establish a relationship between philosophy and literacy, in order to associate the social practices of literacy, lived in the students' context, and to enable dialogue between the contents of the current philosophical tradition, thus broadening the students' interpretive universe. As a research methodology, the ethnographic strategy in the school environment combined with the efficient use of reading and writing was considered as an artifact to aid in the apprehension, comprehension and reading of the world based on the philosophical concepts inherited by tradition. Aiming at this, to enable the dialogue between the socio-cultural context of the students, and, therefore, the re-signification of the content taught in the classroom, especially those of a philosophical nature.